2014
DOI: 10.5588/ijtld.13.0688
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for treatment default in close contacts with latent tuberculous infection

Abstract: Objective To characterize risk factors for non-completion of treatment for latent tuberculosis infection (LTBI). Secondarily, to assess the impact of LTBI treatment regimen on subsequent risk of tuberculosis. Methods Close contacts of adults (≥15 years) with pulmonary tuberculosis were prospectively enrolled in a multi-center study in the U.S. and Canada from January 2002–December 2006. Close contacts to TB patients were screened and cross-matched with tuberculosis registries to identify those who developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
3
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 22 publications
2
33
3
2
Order By: Relevance
“…In our study, the factors associated with non‐compliance with recommendations were being of foreign origin, alcoholism, being recommended to repeat the TST at 3 months, being recommended LTBIT, an index case aged under 35 years, and a smear‐positive index case. These factors have previously been identified by other authors as being associated with non‐compliance. Non‐compliance among foreigners may often be due to their working conditions, because they are often employed in precarious jobs where taking time off to attend the recommended appointments could result in loss of earnings or employment .…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…In our study, the factors associated with non‐compliance with recommendations were being of foreign origin, alcoholism, being recommended to repeat the TST at 3 months, being recommended LTBIT, an index case aged under 35 years, and a smear‐positive index case. These factors have previously been identified by other authors as being associated with non‐compliance. Non‐compliance among foreigners may often be due to their working conditions, because they are often employed in precarious jobs where taking time off to attend the recommended appointments could result in loss of earnings or employment .…”
Section: Discussionmentioning
confidence: 53%
“…However, despite the importance of contact tracing, remarkably few studies in the literature have reported on the results of contact monitoring from initial screening until the end of treatment . Some studies have analysed monitoring from the first appointment until the third month, whereas others have focused solely on monitoring treatment of contacts with LTBI …”
Section: Introductionmentioning
confidence: 99%
“…Refugees and other persons born outside the country, pregnant women, and health care workers were less likely to initiate treatment. Initiation rates were higher where specific strategies to improve adherence were used, discussed below …”
Section: Resultsmentioning
confidence: 99%
“…There are different risk factors for the non-compliance. Race was found to be the most common risk factor; Hispanics, people born outside the US and Canadians had lower rates of medication compliance, whereas blacks had the highest compliance [6].…”
Section: Investigationmentioning
confidence: 98%